Luminescent Zn(II) and Cd(II) coordination polymers based on naphthalene tetracarboxylic acid and 4, 4'-bipyridine for sensing of nitrobenzene, Fe3+ and Cr2O72− ions. Issue 19 (17th December 2022) - Wang, Jun-Jie; Han, Xue-Lian; Chen, Jing-Xia; Li, Ji-Xiang; Zuo, Meng-Juan; Chen, Wan-Ying; Chen, Li-Mei; Jin, Chao-Yue
Abstract: Two luminescent Zn(II) and Cd(II) metal-organic frameworks (MOFs) containing 1, 4, 5, 8-naphthalene tetracarboxylic acid (H4 L') and 4, 4'-bipyridine (4bpy), [ZnL(4bpy)0.5 (DMA)]n (1 ) and [CdL(4bpy)0.5 ]n (2 ) (L = 1, 8-monoanhydride-1, 4, 5, 8-naphthalenetetracarboxylate, DMA = N, N-dimethyl acetamide), were synthesized and characterized through X-ray diffraction, IR, and UV-Vis spectroscopy. 1 shows a 1D linear chain structure, while 2 shows a 2D baluster structure. Both show multiple H bonding and π-stacking interactions. Both compounds show ligand-based luminescence in the range 400-500 nm with contributions from both ligands. The luminescence is strongly dependent on the presence of potentially coordinating molecules. Luminescence quenching experiments show good sensitivities in detecting nitrobenzene (NB), Fe 3+ and Cr2 O7 2− . Abstract : UF0001